(untitled) (Journal of the Bangladesh Agricultural University, 2013)
The experiment was conducted at Bangladesh Agricultural University Dairy Farm to study the effect of fish meal (FM) on growth and reproductive performances of crossbred heifers. The experiment was designed into four treatment (T0=0% FM; T1=5% FM; T2=7.5% FM and T3 =10% FM) groups having initial weight 231.33 ± 32.39, 241.00 ± 46.29, 198.66 ±58.53 and 236.66 ± 31.64 kg, respectively. The average age of the animal is 2 years 9 month. Results of the experiment revealed that there was a significant difference of FM on daily DMI (kg/d). In 90 days period, FM with rice straw based diet had significant effect on daily weight gain (kg/d) of crossbred heifers. DM, CP and CF digestibility (%) differ significantly (p<0.05) among the group. But, the EE, Ash and NFE do not differ significantly. However, there is a tendency to increase digestibility when increase the FM among the Treatment group. Among this group T3 and T1 treatment showed 100% and T0 treatment 66% estrus and T1 did not showed estrus. Based on above findings, it may be concluded that supplementation of FM with Rice straw based diet can be the best options for feeding crossbred heifers to obtain better performances in terms of dry matter intake, digestibility, daily weight gain and reproductive performance especially estrus. DOI: http://dx.doi.org/10.3329/jbau.v10i2.14917 J. Bangladesh Agril. Univ. 10(2): 261-266, 2012